Mut'ah Marriage Position In The National Law System And Islamic Law - ainul yakin (Veteran Justice Journal, 2022)
This article examines the position of mutáh marriage in the national legal system and Islamic law. The background of this study departs from the many phenomena in society regarding the practices of mutáh marriage. Therefore, this article seeks to raise the legal status of mutáh marriages both in terms of legislation and in terms of Islamic law. In Law No. 1 of 1974 it is stated that one of the conditions for a valid marriage is that it must be recorded in state documents. Likewise in Islamic law that one of the goals of marriage is a form of actualizing the perfection of religion and carrying out the sunnah of the Prophet. Keyword: Mutáh Marriage, National Law and Islamic Law